Quand l’état critique est salutaire. Du procès du « décolonialisme » à l’urgence du décentrement - Stéphane Dufoix (Astérion)
For some years now, the French social sciences –sociology in particular– have been undergoing a period of great tension that was essentially characterised by attacks on the “ideological” –and therefore unscientific– character of the discipline and its vulnerability to the invasion of “decolonialism” from the United States. However, most of these accusations are based on approximations, errors, and misunderstandings that need to be corrected in order to distinguish between, for example, the “decolonialism” denounced by neo-republicans –be they political or academic– and “decolonial thought”, which springs from a complex history and whose critical character stems from an epistemological opposition to abstract universalism of the Western type. A quick overview of certain non-Western academic movements shows that a large part of counter-hegemonic thought has adopted a critical stance in order to be able to envisage a new universalism.